The Effect of Giving Letters Versus Card Games and Bincer Games and Learning Motivation on the Language Ability of Early Children - Zubaidatul Aizah; I Nyoman Sudana Degeng; Ibut Priono Leksono (STAI Miftahul Ula Nganjuk, 2025)
This study aimed to investigate the impact of providing letter card games compared to binary games and learning motivation on language skills among early childhood students. The hypothesis posited that there is a significant influence of providing letter card games versus binary games and learning motivation on the language skills of early childhood students at Bintang Sembilan Kindergarten and Kemala Bhayangkari Kindergarten 75 Lamongan in 2022. The study involved 25 students from Bintang Sembilan Kindergarten and 15 students from Kemala Bhayangkari Kindergarten 75 Lamongan. A Random Assignment Posttest Control Group Design was utilized in this research, consisting of two groups: the experimental class and the control class. Data were collected through quasi-experimental methods, allowing for control of variables relevant to the experiment. Data analysis involved the use of the two-way ANOVA test formula, the Normality test, and the Homogeneity test. The results of the study indicated statistical significance across all three tests, confirming the effectiveness of the experimental design. The Pearson test confirmed the alternative hypothesis, concluding that there is indeed an effect of providing letter card games versus binary games, along with learning motivation, on the language skills of early childhood students in Bintang Sembilan Kindergarten and Kemala Bhayangkari Kindergarten 75 Lamongan in 2022